2012
DOI: 10.1128/aem.02088-12
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Bacillus thuringiensis subsp. israelensis in the Field: Evidence for Spore Recycling and Differential Persistence of Toxins in Leaf Litter

Abstract: Bacillus thuringiensis subsp. israelensis is a bioinsecticide increasingly used worldwide for mosquito control. Despite its apparent low level of persistence in the field due to the rapid loss of its insecticidal activity, an increasing number of studies suggested that the recycling of B. thuringiensis subsp. israelensis can occur under specific, unknown conditions. Decaying leaf litters sampled in mosquito breeding sites in the French Rhône-Alpes region several months after a treatment were shown to exhibit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 46 publications
2
42
0
1
Order By: Relevance
“…When 1,000-2,000 larvae were sampled, high sensitive standard bioassays could be performed, but not for all the Cry toxins; bioassays with Bti and Cry4Aa were performed in priority since Cry4Aa is the main toxin persisting in the field after Bti treatment (Tetreau et al 2012a) and with the highest resistance ratio in the Bti -resistant strain described in Tetreau et al (2012b). Lethal concentrations for 50% individuals (LC 50 ) were calculated for each population and each toxin using a probit statistical model with the module "dose" of XLSTAT v.2009.4.06 (Addinsoft).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When 1,000-2,000 larvae were sampled, high sensitive standard bioassays could be performed, but not for all the Cry toxins; bioassays with Bti and Cry4Aa were performed in priority since Cry4Aa is the main toxin persisting in the field after Bti treatment (Tetreau et al 2012a) and with the highest resistance ratio in the Bti -resistant strain described in Tetreau et al (2012b). Lethal concentrations for 50% individuals (LC 50 ) were calculated for each population and each toxin using a probit statistical model with the module "dose" of XLSTAT v.2009.4.06 (Addinsoft).…”
Section: Methodsmentioning
confidence: 99%
“…Recent works on Bti -resistance showed that while levels of resistance to Bti can be low in a laboratory-selected strain (3.5-fold), resistance to each of the Cry toxins tested separately in bioassays can be much higher (up to 60-fold) (Paris et al 2011, Tetreau et al 2012b). Here we present an improved bioassay method consisting in performing distinct bioassays with each of the three Bti Cry toxins on field populations of mosquitoes.…”
mentioning
confidence: 99%
“…israelensis de Barjac ( Bti- H14) was the first Bt strain used as an effective biological control agent against larvae of many mosquito and blackfly species worldwide, with no adverse effects on non-target invertebrates and vertebrates. Several studies have linked the larvicidal activity of Bti to its major Cyt1Aa and Cry4Ba, Cry4Aa, Cry10, Cry11Aa proteins [1, 15, 16]. In Bti -H14, these proteins are all encoded and located on a large plasmid (128 kb) recognized as p Bt oxis [17] and differ in their mosquito toxicity [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…If these crystals are ingested by susceptible insects, they cause serious injuries or death (11). Several researchers have studied the effect of these toxins on the reproduction and growth of the house fly (5,6,11). In this study, we studied the effect of a protein crystal toxin derived from B. thuringiensis serotype H14 (subspecies israelensis) on the larvae of house flies.…”
Section: Discussionmentioning
confidence: 99%
“…During sporulation, this bacterium produces protein crystals (delta endotoxin) that have insecticidal activity (5,6). Several studies have suggested that these toxins, or a mixture of unknown components in the toxins acting together synergically, produce the full toxicity.…”
Section: Introductionmentioning
confidence: 99%